Introduction of Fish and Celery Broth to Prevent Hypertension (DURASI) as an Alternative to Salt in Karangrejo Community, Banyuwangi - Nisa', Nahdhiah Khoirun; Mandagi, Ayik Mirayanti; Eka Sari, Jayanti Dian; Lailiyah, Syifa'ul (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Hypertension is one of the non-communicable diseases (PTM) which isthe main cause of death in society which is a global problem. Hypertension can occuranytime and anywhere without complaints, so this disease is called a silent killer orsilently deadly. One can start to controlling their hypertension by increasing theirknowledge and self-awareness as well as adopting a healthy lifestyle. One way islimiting the consumption of salt according to WHO recommendations, which is 2,400mg/day or the equivalent of one teaspoon. Public Health students from the Facultyof Health and Natural Sciences (FIKKIA) of Universitas Airlangga created DURASIproducts as an alternative to salt to control hypertension. DURASI stands for fish andcelery broth to prevent hypertension. Fish is rich in omega 3 which can lower bloodpressure and celery has hexane extract which plays a role in lowering blood pressureas well as methanol and ethanol extract which can increase blood pressure circulation.At the Kertosari Health Center in 2021 hypertension ranks 1st out of the top 10diseases in the working area of the Kertosari Health Center, including Kerosari Villageand Karangrejo Village. In suppressing hypertension cases in the Karangrejo Village,community service activities were carried out by introducing DURASI products as analternative to salt to the Integrated Development Post (Posbindu) cadres as pioneersof healthy living to prevent hypertension. The DURASI product introduction method iscarried out for Posbindu cadres by means of an approach including counseling, trainingand mentoring. Laboratory test results obtained sodium content of 550 mg/100 gramDURASI. The result of increasing public knowledge in the first measurement wasan average increase of 50% and in the second measurement there was an averageincrease of 7%. The factor that affected the small number of increasing publicunderstanding was the awareness of using DURASI products at home.